Exploring the Composition and Diversity of Handline Fishery Catches in Pulau Panggang - Nurani Khoerunnisa; Hanif Dzulpikah Darojat; Lady Ayu Sri Wijayanti; Mochhamad Ikhsan Cahya Utama; Nora Akbarsyah (JURNAL PESISIR DAN LAUT TROPIS, 2025)
Handline fishing is a traditional fishing method widely used by small-scale fishers in Pulau Panggang, Kepulauan Seribu, due to its efficiency, selectivity, and environmentally friendly nature. This study aims to evaluate the species diversity and catch composition of handline fisheries in Pulau Panggang based on production data from 2021 to 2023. The analyzed data include catch volume, production value, and species composition. The results indicate that narrow-barred Spanish mackerel (Scomberomorus commerson) was the dominant species caught over the three-year period, comprising approximately 30–33% of the total catch, followed by frigate tuna, snapper, and emperor fish. The Shannon-Wiener diversity index revealed a moderate level of species diversity (ranging from 1.411 to 1.960), reflecting a relatively stable community structure. Catch volume and production value fluctuated over the study period, peaking in 2022 and declining in 2023. These findings highlight the importance of data-driven management and policies that account for seasonal variability and fishing pressure to ensure the sustainability of the handline fishery in the region. Keywords: catch, fish diversity, handline fishing, Pulau Panggang   Abstrak Pancing ulur merupakan alat tangkap tradisional yang banyak digunakan nelayan skala kecil di Pulau Panggang Kepulauan Seribu karena efisien, selektif, dan ramah lingkungan. Penelitian ini bertujuan untuk mengevaluasi keanekaragaman dan komposisi hasil tangkapan pancing ulur di Pulau Panggang, Kepulauan Seribu, berdasarkan data produksi tahun 2021 hingga 2023. Data yang dianalisis mencakup volume tangkapan, nilai produksi, serta jenis spesies hasil tangkapan. Hasil penelitian menunjukkan bahwa ikan tenggiri (Scomberomorus commerson) merupakan spesies dominan selama tiga tahun berturut-turut dengan persentase sekitar 30–33%, diikuti oleh tongkol, kakap, dan lencam. Indeks keanekaragaman Shannon-Wiener menunjukkan tingkat keragaman sedang (nilai 1,411-1,960), yang mencerminkan struktur komunitas yang cukup stabil. Produksi dan nilai hasil tangkapan mengalami fluktuasi, dengan puncak tertinggi pada tahun 2022 dan penurunan pada 2023. Temuan ini menunjukkan pentingnya pengelolaan berbasis data dan kebijakan yang mempertimbangkan musim serta tekanan penangkapan untuk menjaga keberlanjutan perikanan. Kata kunci: hasil tangkapan, keanekaragaman ikan, pancing ulur, Pulau Panggang